Knowledge, Perception and Practice of Telemedicine among Undergraduate Medical Students at a Tertiary Care Teaching Hospital - Vithalani, Ami; Barot, Preksha; Shukla, Apexa; Patel, Hitesh; Dave, Darshan (Al-Sihah : The Public Health Science Journal, 2024)
Telemedicine is crucial in supporting the healthcare sector in developing countries as it can assist in various scenarios, such as low physician-to-population ratios, lack of access to specialty physicians, and patient and physician needs in remote areas. The study aimed to assess the knowledge, perception, and practice of telemedicine among undergraduate medical students, recognizing the importance of equipping future healthcare professionals with the necessary skills and understanding of this technology. A cross-sectional study was conducted among 307 undergraduate medical students at a tertiary care teaching hospital. A structured questionnaire was used to collect data on demographic information, computer literacy, knowledge, perception, and practice of telemedicine. Data entry and analysis were done using Microsoft Office Excel 2010. The mean, percentage, and standard deviation were calculated to describe the characteristics of respondents. This study found that 75.8% of participants were aware of telemedicine; however, only 18.8% recognized its use for prescribing drugs. Additionally, 59.9% had a low level of perception towards telemedicine. Although 45% agreed to incorporate telemedicine into medical education, 61% preferred traditional hospital visits due to concerns about information, expertise, and technical challenges. The study emphasizes the imperative for telemedicine training to address the existing knowledge gap. It underscores the critical importance of integrating telemedicine education into medical curricula at an early stage.